PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL SERTA DAMPAKNYA PADA KINERJA KARYAWAN (STUDI KASUS PADA MANAJEMEN PUSAT WAROENG SPESIAL SAMBAL YOGYAKARTA) - Tri Wahyuni; Soni Kurniawan (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this study is to describe (1) the effect of motivation on employee job satisfaction center management Waroeng Spesial Sambal Yogyakarta, (2) the effect of motivation on employee performance center management Waroeng Spesial Sambal Yogyakarta, (3) the effect of job satisfaction on employee performance center management Waroeng Spesial Sambal Yogyakarta, (4) the effect of motivation on organizational commitment of employees, (5) the effect of job satisfaction on organizational commitment of employees, and (6) the effect of organizational commitment on employee performance center management Waroeng Spesial Sambal Yogyakarta. This research is classified in research exsplanatory research. The population is 102 employees of center management Waroeng Spesial Sambal Yogyakarta. The samples number are 79 respondents and used probability techniques slovin method. Methods of data collection is done by the media questionnaires, while data analysis techniques used simple linear regression analysis and multiple linear regression analysis. The results showed that (1) motivation effect on employee job satisfaction, (2) motivation effect on employee performance, (3) job satisfaction does not affect the employee performance, (4) motivation does not affect the organizational commitment of employees, (5) job satisfaction affect the organizational commitment of employees, and (6) organizational commitment effect on employee performance. Kata Kunci: motivation, job satisfaction, organizational commitment, and employee performance, center management Waroeng Spesial Sambal Yogyakarta.